PENGARUH TRANSFER PRICING, THIN CAPITALIZATION DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE DENGAN SALES GROWTH SEBAGAI VARIABEL MODERASI - Alamsyah, Sustari; Sarra, Hustna Dara; Susilawati, Desi (Universitas Muhammadiyah Tangerang, 2024)
This research aims to determine the effect of Transfer Pricing, Thin Capitalization and Capital Intensity on Tax Avoidance with Sales Growth as a Moderating Variable. The population used was IDX companies in the food and beverage sector for 2018-2022 with a sampling technique using purposive sampling and 12 selected companies were obtained. Quantitative research design with the type of relationship between variables being causal (cause and effect). This research also assumes that there are other variables that moderate the relationship between the independent variable and the dependent. for partial hypothesis testing using panel data regression and for moderation testing using the moderated regretion analysis (MRA) test. The research results show that the thin capital, capital intensity and sales growth variables have an effect on tax avoidance, while transfer pricing has no effect on tax avoidance. for the moderation test, it was found that the sales growth variable was only able to moderate the effect of thin capitalization on tax avoidance, while the transfer pricing and capital intensity variables were not able to moderate it.